(untitled) (Italian Journal of Public Health, 2010)
This cross sectional study was conducted to assess the knowledge and practice of preventive measures in occupational exposure to blood and body fluids among nurses in a university hospital in the UAE. A pre-tested structured self administered questionnaire was used for data collection. The mean age of the respondents was 29.59±5.96 years and the median duration of clinical experience was 63 months ranging from 10 months to 264 months. Of the total, 25.7% reported having had exposure to splashes of blood and body fluids into the eyes or mouth. 98% of nurses reported that if there had been any splash of blood or body fluids it is important to rinse with plenty of running water. 98% knew that the ideal method of disposal of sharp waste (e.g. hypodermic needles) was to put it in a puncture proof container immediately after use. 93.1% of the nurses reported that the needle pricks, cuts or scratches should be bled by squeezing. 93% habitually used masks always during surgery and 80.4% always wore goggles during surgery. With regard to recapping of needles, 44.6% were aware that needles should be recapped by single hand technique after use and among them 93.3% practiced this method; there was a statistically significant association (p<0.001) between the awareness and practice, but not between years of experience and needle recapping technique after use. The knowledge among nurses about preventive measures in occupational exposure to blood and body fluids is adequate but in practice it is inadequate.